(untitled) (Research, Society and Development, 2020)
The present study evaluated the toxicity and larvicidal activity of essential oil (EO) of Alpinia zerumbet leaves. The (EO) was extracted by hydrodistillation at 100°C for 3h and the physicochemical parameters were determined using the Brazilian Pharmacopoeia. Toxicity was performed through the bioassay of Artemia salina Leach, then larvicidal activity was evaluated against Aedes aegypti. LC50 was calculated for toxicity and larvicidal activity against mosquito larvae based on the Reed-Muench method. The EO was classified for toxicity and the Dolabela criterion was used. In the toxicity bioassay, LC50 321.15 mg L-1 was classified as nontoxic. Larvicidal activity against Aedes aegypti showed 50.70 mg L-1 according to EO. Total phenolics resulted in 513.574 mg EAT g-1. The EO presented satisfactory results against the microorganisms tested, revealing its efficiency in combating and controlling pathogenic microorganisms and larvicides.